Traditional Chinese Medicine Reduces the Incidence of Chemotherapy-Induced Stroke: A Five-Year Nationwide Population-Based Cohort Study From Taiwan - Chien-Chen Huang; Chien-Chen Huang; Yu-Cih Yang; Iona MacDonald; Ching-Yuan Lai; Cheng-Hao Tu; Yi-Hung Chen; Yi-Hung Chen (Frontiers Media S.A., 2021)
Background: Chemotherapy is suspected to be a risk factor for stroke in patients with cancer, athough the results from large-scale studies are controversial. Few strategies are available for reducing the stroke-related risks.Methods: We analyzed stroke incidence rates in Taiwan's Longitudinal Health Insurance database 2000 (LHID2000) for patients aged ≥20 years with newly-diagnosed cancer between Jan 1, 2000 and Dec 31, 2006, who did or did not receive chemotherapy. Moreover, we compared stroke incidence rates among chemotherapy users who did or did not use traditional Chinese medicine. All study participants were followed-up for 5 years or until they had a stroke.Results: In adjusted Kaplan-Meier analysis, the incidence of stroke was higher within the first year of cancer diagnosis among chemotherapy recipients compared with those who did not receive chemotherapy (31.1 vs. 9.75; adjusted subdistribution hazard ratio [sHR] 2.21; 95% confidence interval [CI], 1.52-3.20; p < 0.001). This between-group difference persisted at 4 years of follow-up (13.6 vs. 5.42; adjusted sHR 1.94; 95% CI, 1.53-2.46; p < 0.001). Similarly, the 5-year incidence rate of stroke was significantly lower among chemotherapy recipients using TCM vs. non-TCM users (0.19 vs. 0.46; adjusted sHR 0.45; 95% CI, 0.26-0.79; p < 0.001), as was the mortality rate (adjusted sHR 0.55; 95% CI, 0.44-0.68; p < 0.001).Conclusion: These Taiwanese data suggest that chemotherapy is a risk factor for stroke and that the use of TCM can significantly mitigate this risk. TCM also appears to reduce the mortality risk associated with chemotherapy.